Bad mood food? Increased versus decreased food cue reactivity in anorexia nervosa and bulimia nervosa during negative emotions. (26th June 2021) - Schnepper, Rebekka; Richard, Anna; Georgii, Claudio; Arend, Ann‐Kathrin; Naab, Silke; Voderholzer, Ulrich; Wilhelm, Frank H.; Blechert, Jens
Abstract: Objective: Emotion regulation difficulties in anorexia nervosa (AN) and bulimia nervosa (BN) might underlie bingeing and purging in BN, extreme fasting in AN, or combinations of these symptoms in binge‐purge type AN. In this study, we tested for decreased food cue reactivity in response to negative emotions in AN, and the opposite pattern for BN. Furthermore, we explored subgroup differences (restrictive vs. binge‐purging AN; history of AN in BN). Method: Patients with AN ( n  = 41), BN ( n  = 39), and matched controls ( n  = 70) completed an emotional eating questionnaire. In a laboratory experiment, we induced negative emotions and measured food cue reactivity (pleasantness, desire to eat (DTE), and corrugator muscle activity). Results: AN reported emotional undereating, while BN reported emotional overeating. In the laboratory task, BN showed increased DTE and an appetitive corrugator response during negative emotions, selectively towards high‐calorie foods. AN showed generalized reduced cue reactivity to high‐calorie food regardless of emotional state. This pattern appears to be characteristic of restrictive AN, while cue reactivity of both BN subgroups pointed towards emotional overeating. Conclusions: The emotional over‐ versus undereating framework might help to explain bingeing and restricting along the anorectic‐bulimic disorder spectrum, which calls for novel transdiagnostic theories and subgroup‐specific treatments. Highlights: Emotional eating might be an emotion regulation strategy in both bulimia nervosa (BN) and anorexia nervosa (AN). While AN shows decreased reactivity to food pictures in negative mood, BN shows increased reactivity. These reactions might explain restriction and bingeing symptomatology and have the potential to discriminate between eating disorder subtypes.